A new carbon tax in Portugal: a missed opportunity to achieve the triple dividend? - Pereira, A.; Pereira, R.; Rodrigues,P.G. (Energy Policy, 2016)
In 2014, the Portuguese government appointed a Commission for Environmental Tax Reform that formulated a carbon-tax proposal designed to achieve three dividends: to help Portugal meet the European Union's target for emissions reductions by 2030, to boost long-term employment and GDP above their pre-carbon-tax levels, and to strengthen public finances by lowering public indebtedness. A key feature of this proposal was a judicious set of mixed strategies to recycle all carbon-tax revenues back into the economy. In this note, we show how the carbon tax that the Portuguese Parliament eventually approved deviated from such guidelines, and ultimately failed to achieve the triple dividend. We argue that authorities need to quickly amend the existing legislation to avoid this misguided attempt turning into a missed opportunity to improve environmental, macroeconomic, and fiscal outcomes.